Tasawuf dan Modernisasi: Urgensi Tasawuf Akhlaki pada Masyarakat Modern - Muhammad Nur; Muhammad Iqbal Irham (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2023)
Sufism is a part of Islamic religious teachings. Ethical Sufism is one of the Sufi teachings that can help shape individuals with noble character. Amidst the hedonistic and materialistic lifestyle that has contributed to the moral decline of modern society, the moral aspect of Sufism seeks to balance these opposing forces. By implementing Sufism in contemporary culture, values of goodness and nobility can be instilled, offering a solution to one of the major problems plaguing modern society: the fragmentation of the human soul, something that can undermine one's moral worth. In dealing with this glittering materialism and even neglecting God in one's life, modern life as it is today sometimes reveals undesirable tendencies. The ethical aspect of Sufism, particularly the moral teachings that should be applied in one's daily life to achieve optimal satisfaction, emphasizes the importance of Sufism for contemporary human beings. Learning the teachings of ethical Sufism is a path to developing one's character in a way that honors God, fellow humans, and one's own best interests. Good introspection in facing difficulties, purifying the soul from negative qualities (takhalli), and adorning oneself with praiseworthy qualities are just a few of the positive concepts of ethical Sufism that may form noble traits (tahalli). The teachings of Sufism can serve as a guide for one's actions, a source of normativity, inspiration, and moral compass.Abstrak: Tasawuf adalah bagian dari ajaran agama Islam. Tasawuf akhlaqi merupakan salah satu ajaran sufi yang dapat membantu membentuk manusia yang berakhlak mulia. Berada di tengah gaya hidup hedonistik dan materialistis yang turut menyebabkan kemerosotan moral masyarakat modern, sufisme moralitas berupaya menyeimbangkan antara dua kekuatan yang berlawanan tersebut. Dengan implementasi tasawuf dalam kebudayaan masa kini, nilai-nilai kebaikan dan keluhuran dapat terbentuk, menawarkan solusi atas salah satu persoalan besar yang melanda masyarakat kontemporer: fragmentasi ruh manusia. sesuatu yang dapat menjatuhkan harga dirinya secara moral. Dalam menyikapi materi gemerlap ini dan bahkan mengesampingkan Tuhan dalam hidupnya, kehidupan modern seperti sekarang ini terkadang menampakkan kecenderungan yang tidak terpuji. Tasawuf akhlak, khususnya ajaran-ajaran akhlak yang harus digunakan dalam kehidupan sehari-hari seseorang untuk memperoleh kepuasan yang optimal, menekankan pentingnya tasawuf bagi manusia kontemporer. Mempelajari ajaran tasawuf akhlaqi adalah jalan untuk mengembangkan karakter seseorang dengan cara yang memuliakan Tuhan, sesama manusia, dan kepentingan terbaiknya sendiri. Introspeksi diri yang baik dalam menghadapi kesulitan, membersihkan jiwa dari sifat-sifat yang buruk (takhalli), dan menghiasi diri dengan sifat-sifat yang terpuji hanyalah beberapa dari konsep positif tasawuf akhlaqi yang mungkin membentuk sifat yang mulia (tahalli). Ajaran tasawuf dapat menjadi pedoman bagi tindakan seseorang, sumber normativitas, inspirasi, dan kompas moral.